Dian Fossey : primatologist - Nicholson, Lois, 1949- (Philadelphia : Chelsea House Publshers, 2003)
Profiles the life of the scientist who studied mountain gorillas in central Africa and worked to ensure their survival
References : p. 112-114
Keywords: Fossey, Dian -- Juvenile literature; Fossey, Dian; Primatologists -- United States -- Biography -- Juvenile literature; Zoologists; Scientists; Women -- Biography